2015
DOI: 10.1186/2055-5660-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Save the pig tail

Abstract: Tail biting is a common problem in modern pig production and has a negative impact on both animal welfare and economic result of the farm. Tail biting risk is increased by management and housing practices that fail to meet the basic needs of pigs. Tail docking is commonly used to reduce the risk of tail biting, but tail docking in itself is a welfare problem, as it causes pain to the pigs, and facilitates suboptimal production methods from a welfare point-of-view. When evaluating the cost and benefit of tail d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 41 publications
2
60
0
1
Order By: Relevance
“…The tail biting level (average 2.3 %, median 1 %) on the farms in this is close to what has been reported by Finnish slaughterhouses (2.3 % in 2013, [8]), using the same definition of severity. It needs to be noted however, that this, by definition, only includes severe, clinical cases, and total tail lesion level (including milder lesions) is probably much higher, as reported recently by Harley et al 2014 [5] and in a study of Finnish pigs in 2000 [33].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The tail biting level (average 2.3 %, median 1 %) on the farms in this is close to what has been reported by Finnish slaughterhouses (2.3 % in 2013, [8]), using the same definition of severity. It needs to be noted however, that this, by definition, only includes severe, clinical cases, and total tail lesion level (including milder lesions) is probably much higher, as reported recently by Harley et al 2014 [5] and in a study of Finnish pigs in 2000 [33].…”
Section: Discussionsupporting
confidence: 86%
“…As long as this is the case, it will be very difficult to implement a total ban on tail docking. Instead, it is important to communicate that farmers should not expect tail biting to disappear before tail docking can be banned [8], but that there is a need to find a level with which the producers can manage. This acceptance of a certain level of tail biting might be another factor why Finnish farmers manage with the tail docking ban.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among PHM’s inaugural articles are a review article on tail biting in modern pig production by Anna Valros and Mari Heinonen [5], a research article on serum haptoglobin dynamics and a commercial porcine circovirus type 2 vaccine by Lorenzo Fraile and colleagues [6], and a research article comparing lesions found in pigs under organic/free-range and conventional/indoor production conditions by Lis Alban and colleagues at the Danish Agriculture & Food Council [7]. …”
Section: Editorialmentioning
confidence: 99%